Podatek VAT w warunkach akcesji Polski do Unii Europejskiej - Famulska, Teresa (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
VAT in Poland generally conforms to the European Union Standards. In numerous detailed issues it is incompliant with the 6th Directive. The ultimate destination of the harmonisation of regulations concerning the VAT is to provide Polish entrepreneurs with business conditions that are comparable with those that are characteristic of other countries creating the common market. In the future some improvements of Polish fiscal regulations quality may be expected. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 171-179